Astigmatism following retinal detachment surgery. Issue 5 (May 1983) - Goel, R; Crewdson, J; Chignell, A H
Abstract : Eighty-three patients on whom successful retinal detachment had been performed were studied to note astigmatic changes following surgery. In the majority of cases the errors following such surgery are of no great clinical importance. However, in some situations a high degree of astigmatism may be produced. This study showed that these sequelae are particularly likely after radial buckling procedures, and surgeons favouring these techniques should be aware that astigmatic errors can be induced. The astigmatic errors may persist for several years after surgery.